From Podcasts to Comment Sections: An Analysis of Hate Speech and the Development of Netizens’ Language in Digital Spaces - Abidah, Ulya; Umaya, Nazla Maharani; Septiana, Ika (Jurnal Ragam Pengabdian, 2026)
The advancement of digital communication has transformed the way language is produced, shared, and interpreted in online spaces. This transformation has also contributed to the emergence of hate speech, particularly in digital content involving public figures with large audiences. This study aims to describe the forms of hate speech as illocutionary speech acts in Deddy Corbuzier's podcast and to analyze their implications for the development of netizens' language in digital spaces. Using a descriptive qualitative approach, data were collected from two podcast episodes and related YouTube comments through documentation, observation, and note-taking techniques, then analyzed based on Austin and Searle's speech act theories. The findings reveal six forms of hate speech—insult, defamation, unpleasant acts, provocation, incitement, and misinformation—expressed through assertive, directive, expressive, commissive, and declarative speech acts, with expressive acts being the most dominant. Hate speech in the podcast ranges from implicit forms delivered through humor (D1) to more explicit forms through criticism and argumentation (D2). Netizens' comments demonstrate acceptance, reproduction, and modification of these linguistic patterns, indicating that podcast discourse contributes to the normalization and reinforcement of hateful language in digital spaces. This study highlights the importance of digital and language literacy in fostering ethical and responsible online communication.